Taxonomic turnover and abundance in Cretaceous to Tertiary wood floras of Antarctica: implications for changes in forest ecology - Cantrill, David J.; Poole, Imogen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
Based on the temporal distribution, abundance, and taxonomic composition of wood floras, four phases of vegetation development are recognized through the Cretaceous to Early Tertiary of the Antarctic Peninsula: (1) Aptian to Albian communities dominated by podocarpaceous, araucarian, and minor taxodiaceous/cupressaceous conifers with rare extinct gymnosperms (Sahnioxylon). (2) Progressive replacement of these communities in ?Cenomanian to Santonian times by angiosperms, most without modern analogues. (3) Increasing dominance of angiosperms becoming important both in terms of diversity and abundance towards the mid-Late Cretaceous. (4) Modernization of the flora during the Campanian to Maastrichtian with the extinction of earlier forms, appearance of the Nothofagaceae and diversification of associated elements. These patterns broadly follow trends seen in the leaf and palynological record but with some important differences. During the Cretaceous, conifer composition undergoes a change whereby Phyllocladoxylon-type woods increase relative to the older Podocarpoxylon forms. During the Paleocene to Eocene period, a marked extinction in wood types occurs associated with an increase in the abundance of nothofagaceous wood. Detailed examination of wood abundance and distributions from sections within Maastrichtian and Paleocene formations points to strong environmental control on taxonomic compositions. Similar differences are encountered when comparing coeval floras from different geographic regions and palaeoenvironments.
Keywords: Antarktis; flora; geologi; paleobotanikk; paleogeografi; paleontologi

Environmental aspects of the 2000/2001 Norwegian Antarctic research expedition - Njåstad, Birgit (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Antarktistraktaten; Dronning Maud Land; NARE 2000/01; avfallshåndtering; fauna; flora; forurensning; kartlegging; miljøvern